درجة امتلاك معلمي العلوم الطبيعية في مرحلة التعليم الأساسي (الحلقة الثانية) كفايات تكنولوجيا التعليم وممارستها (دراسة ميدانية في مدينة دمشق) - ديب, أوصاف; المحمد, أحمد عباس (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى معرفة درجة توافر كفايات تكنولوجيا التعليم لمعلمي العلوم الطبيعية في مدارس مرحلة التعليم الأساسي (الحلقة الثانية) ودرجة ممارستهم لها. تكون مجتمع البحث من جميع معلمي العلوم الطبيعية في مدارس مرحلة التعليم الأساسي (الحلقة الثانية) وعددهم (106) واعتبروا جميعاً عينة البحث. وقد صممت استبانة تكونت في صورتها النهائية من (56) كفاية في سبعة مجالات هي: مجال تصميم التدريس، واستراتيجيات التدريس، واختيار التقنيات التعليمية، واستخدام التقنيات التعليمية، واستخدام الأجهزة التعليمية، وخدمات مركز تقنيات التعليم، ومجال التقويم. وبعد توزيع الاستبانة وتفريغها وتحليلها، توصل البحث إلى عدة نتائج من أهمها: (31) كفاية من مجموع الكفايات متوافرة بدرجة كبيرة حيث حازت على متوسط حسابي يتراوح بين (79.2) و (67.2) من أهمها العناصر في مجال استخدام الأجهزة التعليمية واستخدام التقنيات التعليمية. (25) كفاية من مجموع الكفايات متوافرة بدرجة متوسطة بمعدل (66.2) و (5.2) من أهمها العناصر المتعلقة باختيار التقنيات التعليمية. وجود (26) كفاية من مجموع الكفايات يمارسها معلمي العلوم الطبيعية بدرجة كبيرة تمثل ما نسبته (46.43%). وجود ارتباط موجب ذي دلالة إحصائية بين توافر هذه الكفايات لدى معلمي العلوم الطبيعية ودرجة ممارستهم لها بلغ (96,0) وهذا يشير أنه كلما زاد توافر الكفايات لدى معلمي العلوم الطبيعية تزداد درجة ممارستهم لها. وجود فروق ذات دلالة احصائية في درجة ممارسة المعلمين لكفايات تكنولوجيا التعليم تعزى لمتغير سنوات الخبرة لصالح المعلمين ذوي الخبرة أقل من (10) سنوات. وجود فروق ذات دلالة احصائية في درجة ممارسة المعلمين لكفايات تكنولوجيا التعليم تعزى لمتغير المؤهل العلمي لصالح المعلمين ذوي المؤهل العلمي الأعلى (دبلوم التأهيل التربوي). The research aimed at identifying the degree of the availability of teaching technology adequacies among teachers (Second cycle) of basic education schools. In addition, it aimed at identifying the degree of practicing these adequacies by teachers. The research subjects consisted from all Biology teachers in all (Second cycle) of basic education schools and were (106) teachers who represented the sample of the research. A questionnaire was prepared and consisted in its final shape of (56) adequacies divided into (7) fields as follows: Designing instruction, instruction strategies, choosing teaching technologies, using teaching technologies, using teaching devices, services of teaching technologies center and assessment. After analyzing the answers to the questionnaire, the results indicated the following: - (31) of the overall adequacies were available in a great extent, where their average was (2.76 – 2.79), the most important of which were in the fields of using teaching devices and teaching technologies. - (25) of the overall adequacies were available in an average extent (2.66) and (2.5), the most important of which were in the field of choosing teaching technologies. - (26) of the overall adequacies were practiced in a great extent by the Biology teachers, the rate was (46.43 %). - There was a significant statistical positive correlation between the availability of these adequacies among Biology teachers and the extent of practicing them by those teachers (0.96), which indicates that whenever these adequacies are available for Biology teachers, the extent of practicing them increases. - There were significant statistical differences between the degree of Practicing Teaching Technology Adequacies by Biology Teachers according to the variable of experience difference in favor of the teachers who had less than (10) years of experience. - There were significant statistical differences between the degree Practicing Teaching Technology Adequacies by Biology Teachers according to the variable of qualification differences in favor of the teachers who had more qualifications.